Gross Parameters of Litter’s Model when Comparing Dietary Composition in Maternal Rats - Shahid Maqbool Korai, Devi Kumari, Nadeem Ul Haque, Sara Sughra, Muhammad Ahmed Azmi, Hina Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Comparing gross parameters of litters on the basis of different dietary composition Methodology: An experimental study consisting of 12 female albino rats was conducted at Al-Tibri medical college. The albino rats were divided into three different groups based on the diet they were to be given, Group A was the control group placed on normal animal diet, Group B placed on high carbohydrate diet, and Group C placed on High fat diet. Gross parameters of the litters produced by the albino rats were studied which included weight and the length of the litters Results: The weight of litters on the 1st, 21st, and 35th day was 5.0 ± 0.0, 44.8 ± 0.83, 70.0 ± 1.22 for group A, 5.4 ± 0.54, 42.0 ± 2.12, 73.4 ± 2.30 for group B, and 5.0 ± 0.0, 40.2 ± 0.44, and 80.6 ± 1.34 for Group C, with significant difference being seen when comparing Group A with Group C on the 21st (p<0.001), and 35th day (<0.001). Parameters of length of litters, also showed no significant difference. Conclusion: Most of the gross parameters of litters showed no significant difference between different diets. Keywords: High fat diet,